Prevention of Cerebral Small Vessel Disease - Smith, Eric E. (Seminars in Neurology, 2017)
Cerebral small vessel disease can cause either ischemic stroke or intracerebral hemorrhage. Accounting for up to 25% of all strokes, it is also the second biggest contributor to the risk of dementia, and is the most common incidentally discovered finding on brain imaging. There are two main causes of cerebral small vessel disease: arteriolosclerotic small vessel disease (with hypertension as the main modifiable risk factor) and cerebral amyloid angiopathy (predominantly caused by β-amyloid deposits limited to the cerebral small arteries, arterioles, and capillaries). Prevention should include the treatment of hypertension and diabetes, if present, and the modification of lifestyle factors such as obesity and poor nutrition. Patients with small subcortical ischemic strokes should be treated with antithrombotics; dual antiplatelet therapy may be more effective than aspirin for the first 3 weeks following acute stroke, but is not more effective than aspirin for long-term prevention. Unresolved questions include the effectiveness of nonaspirin prevention strategies to prevent early recurrence or stroke extension in small subcortical ischemic stroke, and whether symptomatic or silent small vessel disease should influence decisions regarding selection for carotid revascularization or anticoagulation for atrial fibrillation. There is an unmet need for disease-modifying preventive therapies for cerebral amyloid angiopathy, the second most-common cause of spontaneous intracerebral hemorrhage.
Keywords: ischemic stroke; prevention; leukoaraiosis; lacunar infarct; lacunar syndrome; intracerebral hemorrhage; cerebral amyloid angiopathy